Households' willingness to pay for river-transported nutrients: insights for floodplain conservation in Tanzania. - Bigirwa, Daudi; Philip, Damas; Mombo, Felister (Environmental Management, 2025)
Despite the crucial role of river-transported nutrients in supporting floodplain agriculture, their economic value remains largely unrecognized in Tanzania, as they are often perceived as free public goods not traded in markets. As a result, their value is overlooked in agricultural production decisions, leading to the overexploitation of floodplains. This study employs a choice experiment method to estimate households' willingness to pay for nutrients transported by the Rufiji River to floodplain farms in the Lower Rufiji Sub-Basin. A simple random sampling approach was used to select 391 households in Rufiji District. The choice experiment included four attributes: nutrient availability, cultivated land area, environmental conservation programs, and payment. Data were collected through a household survey using choice cards and analyzed using both conditional and random parameter logit models. The findings reveal that households are willing to pay TZS 769.20 ($0.29) per acre per year for a 25% increase in nutrient availability, TZS 452.30 ($0.17) per acre per year for environmental conservation programs, and TZS 227.60 ($0.086) per acre per year for a 10% expansion in cultivated land area. In total, they are willing to pay TZS 1,449.10 ($0.55) annually for each acre of farm benefiting from river-transported nutrients. These results provide insights into the shadow price of river-transported nutrients, which could inform policies aimed at recognizing their economic value. To address their current undervaluation and enhance floodplain conservation efforts, this study recommends that policy makers incorporate the estimated value into economic decision-making processes, particularly those related to floodplain agriculture.